The Character Education in Topeng Malangan Dance Tradition According Transpersonal Psychology Perspective - Kukuh Setyo Pambudi (Ilomata International Journal of Social Science, 2020)
The aim of this research is to uncover the presence of character building in Topeng Malangan dance tradition according to Transpersonal Psychology perspective. This tradition is one of the art cultural heritage that exclusively from Malang and has some rituals as Silem (meditation) and Suguh. There is something unknown beyond human personality which is connected with spirituality so it is correlated with human’s character building. Topeng Malangan dance tradition and all of the rituals inside have contribution and correlation with the character building in the dancer. This research is using qualitative research method with ethnography. It founds that sub-personality and some objects in transpersonal psychology has significant result in building character education at Malang mask dance.